2023
DOI: 10.1002/fsn3.3650
|View full text |Cite
|
Sign up to set email alerts
|

Wheat germ, a byproduct of the wheat milling industry, as a beneficial source of anti‐aging polyamines: A quantitative comparison of various forms

Maryam Mohajeri,
Seyed Abdulmajid Ayatollahi,
Farzad Kobarfard
et al.

Abstract: Polyamines have received a lot of attention since the 1990s because of their anti‐aging, anti‐chronic disease, and proliferative effects. Wheat germ was reported as one of the natural sources of high polyamine, especially spermidine. The current study used three types of wheat germ: group A was industrially separated germ from whole grain, group B was the commercially available germinated wheat germ, and group C was manually separated wheat germ from germinated grain. The polyamine content of putrescine, sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Derivatization and analysis were carried out in accordance with our earlier work ( 33 ). Briefly, a 15 mL falcon tube containing 2 mL of toluene, 1 mL of phosphate buffer (0.5 M, pH 12), and 100 μL of IBCF was filled with 1 mL of the sample solution (100 mg/mL water) and 10 μL of 1, 6 diaminohexane solution (10 mg/mL water).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Derivatization and analysis were carried out in accordance with our earlier work ( 33 ). Briefly, a 15 mL falcon tube containing 2 mL of toluene, 1 mL of phosphate buffer (0.5 M, pH 12), and 100 μL of IBCF was filled with 1 mL of the sample solution (100 mg/mL water) and 10 μL of 1, 6 diaminohexane solution (10 mg/mL water).…”
Section: Methodsmentioning
confidence: 99%
“…The following conditions were used throughout the analysis: The following parameters were used for mass spectrometry: spray voltage of 5.0 kV, capillary temperature of 320°C, gas flow rate of 8 L/min, and capillary voltage of 32 V. All analytes were found in positive mode during measurements of multiple reaction monitoring (MRM). Table 1 lists the analyte’s ideal analytical conditions ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding to that, previous studies have reported the anti-aging, anti-chronic disease, and proliferative effects of wheat germ [3]. Wheat germ is also known as an ergogenic aid due to its vitamin-E-rich content that can improve athlete performance [4].…”
Section: Introductionmentioning
confidence: 99%